Assessment of Sleep Quality and Occupational Fatigue (A cross-sectional study among nurses working in public hospitals affiliated to Ilam University of Medical Sciences) - Mohammad Amin RASHIDI; Meghdad KAZEMI; Mehrdad KAZEMI; Amir Hossein RASHIDI; Majid SEIFIFARD (بهداشت کار و ارتقای سلامت, 2021)
Abstract Introduction: Fatigue is defined as extreme weakness and exhaustion by work and physical or mental effort. Sleep disturbances are among the most important causes of fatigue among people in various occupational societies. The aim of this study was to determine the relationship of occupational fatigue with sleep quality and factors affecting it among nurses working in governmental hospitals. Methods: This cross-sectional study was conducted on 240 nurses working in public hospitals selected by convenience sampling method during a two-month period. In order to collect data, the Fatigue Exhaustion / Fatigue Recovery Questionnaire (OFER-15) and the Pittsburgh Sleep Quality Questionnaire (PSQI-18) were administered. The data were analyzed using SPSS software version 16. Furthermore, Chi-Square, Spearman’s correlation, Independent Sample T-test, and one–way analysis of variance were run. Results: In this study, 55% and 70% of the participants were at inappropriate sleep quality status and the moderate level of occupational excessive fatigue, respectively. Spearman’s correlation test showed a direct and significant correlation between occupational excessive fatigue and sleep quality (p<0.5). Conclusion: Given the significant correlation between sleep quality and fatigue in this research, sleep quality can be used as a predictive variable of excessive occupational fatigue.